Highlighting Verbal Abuse of Tourists through Pragmatic Analysis: A Case Study of a South Korean YouTuber in Bunaken, Indonesia - Rahmawati Rahmawati; Andi Muh. Ruum Sya’baan; Fina Amalia Masri; Arman Arman (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2025)
This study aims to analyze the phenomenon of verbal harassment against female tourists using a pragmatic analysis approach. The focus of this study is the interaction between a South Korean YouTuber, Jiah, and two local men in Bunaken, North Sulawesi. This study uses speech theory (Austin & Searle), speech implicature (Grice), and politeness in language (Brown & Levinson) to examine how everyday speech can encode the implicit meaning of harassment. The research method used is qualitative descriptive with pragmatic discourse analysis techniques. Data was obtained from Jiah's video transcript entitled